ANALISIS PENGARUH PENGUMUMAN DIVIDEN TUNAI TERHADAP ABNORMAL RETURN DAN VARIABILITAS TINGKAT KEUNTUNGAN SAHAM - Tastaftian, Muftiai; Khoiruddin, Moh. (Management Analysis Journal, 2015)
The purpose of this research is to explain the reaction of markets to the dividend cash announcement on all companies share listed on the Sharia Effect List. The other goal is to explain the difference of abnormal return and security return variability (SRV) on the period before, during and after period ex-dividend date in 2014. This research used the event study, which was conducted observation of abnormal return and security return variability during the event period, i.e. before 10 days up to 10 days after the dividend cash announcement. The population in this research are all companies share listed on the Sharia Effect List (DES) in 2014. The sampling technique was conducted with a purposive sampling method and obtained a sample of 135. Based on the result of differential tests analysis showed that there are difference abnormal return on the period before-at the moment, after-at the moment and before-after and security return variability variable on the period before-after the dividend cash announcement. However, the security return variability (SRV) on the period before-after announcement showed that there are no difference.